Adolescents' sources for food safety knowledge and trust. Issue 3 (5th March 2018) - Lange, Marie; Göranzon, Helen; Fleig, Lena; Marklinder, Ingela
Abstract : Purpose: The purpose of this paper is to investigate where students in a Swedish compulsory school acquire their knowledge of food safety and how trustworthy they deem them to be. Design/methodology/approach: A survey of students' self-reported sources of and trust in food safety knowledge was performed. A student response system was used for data collection, and the students were asked to answer questions presented on a PowerPoint presentation using a small wireless handheld device: a clicker. A questionnaire with 24 questions was used, and the responses were collected at 18 different schools with a total of 529 participants attending school Year 9. Findings: Mothers were reported as being the most important source of food safety knowledge (38 per cent), especially among girls, and were also given high credibility (36 per cent). Boys reported trusting home and consumer studies (HCS), fathers and media to a higher extent. Girls reported cooking at home more often but, for all students, it was more common to rarely or never cook at home, which is why HCS teaching can be seen as valuable for many students. HCS teaching needs to be improved in order to raise its credibility. About half of the students (51 per cent) reported to have the highest trust for their source of knowledge. Research limitations/implications: The students could only choose one source of knowledge and trust, although it is usual to learn from many different sources. Practical implications: HCS teaching needs to get higher credibility among students as a counterweight against other sources. Social implications: Educated consumers could influence their health. Originality/value: Limited research has been performed on food safety knowledge among adolescents.